Variation in ascending thoracic aorta position: An analysis by computed tomography - Koen, J.G.; Janson, J.T. (SA Heart Journal, 2021)
Background: There is no evidence in current literature that demonstrates the prevalence of ascending thoracic aortic variation in relation to the sternum in the general, or diseased population. This measurement has become an important factor in decision-making for Trans- Catheter Aortic Valve Implantation (TAVI) and Minimally Invasive Cardiac Surgery (MICS). Methods: We conducted a cross-sectional study in Cape Town, South Africa. We evaluated the Thoracic CT scans of pre-selected TAVI patients (n=25) and compared these to Thoracic CT scans from the same general population (n=100). Three parameters of ascending thoracic aorta variations were measured. Results: Mean aorta distance from sternum was 28.01mm (95% CI: 24.56 - 31.48) in cases and 27.34mm (95% CI: 25.49 - 29.20) in controls (p<0.001). The mean position of the aorta relative to the sternum, favoured the aorta being less than 50% of its diameter to the right, in both groups. Aorto-ventricular angle showed a mean angle (degrees) of 47.92 (95% CI: 44.36 - 51.23) in cases and 37.06 (95% CI: 35.03 - 39.09) in controls. Subgroup analysis for age >60 years revealed no difference between groups (p=0.314). An overall linear relationship of aortoventricular angle, compared to age, was demonstrated. Conclusion: Statistical analysis of ascending thoracic aorta position indicates that patients presenting for aortic valve surgery, especially older patients (>70 years), have favourable anatomy for MICS through a right thoracotomy. The aortic distance from the sternum was larger in the exposed group >60 years. Aortic valve disease does not cause variation in aorto-ventricular angle. The aorto-ventricular angle increases linearly with age, in both groups.